1982
DOI: 10.1128/iai.35.1.79-85.1982
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for mannose-mediated adherence of Candida albicans to human buccal cells in vitro

Abstract: Various lectins and sugars were used to study the possible role of saccharide-containing moieties on the surface of Candida albicans and human buccal cells in the adherence of this yeast to mucosal surfaces. The lectins possessed affinities for several different sugar moieties and were used to pretreat C. albicans or buccal cells before mixing and incubating in the adherence assay. It was found that concanavalin A, a lectin that recognizes mannose and glucose, inhibited adherence of the pretreated yeasts to bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(68 citation statements)
references
References 25 publications
(31 reference statements)
6
61
1
Order By: Relevance
“…The level of adhesion of C. albicans to the buccal cells was assessed by the method of Sandin et al (26). Briefly, 0.2 ml of a mixed suspension of buccal cells (10 5 /ml) and yeast cells (10 7 /ml) was incubated with shaking at 180 r.p.m.…”
Section: Candidal Adhesionmentioning
confidence: 99%
“…The level of adhesion of C. albicans to the buccal cells was assessed by the method of Sandin et al (26). Briefly, 0.2 ml of a mixed suspension of buccal cells (10 5 /ml) and yeast cells (10 7 /ml) was incubated with shaking at 180 r.p.m.…”
Section: Candidal Adhesionmentioning
confidence: 99%
“…[27] who demonstrated that germinated C. a/bicans had significantly greater adherence to BEC than blastospores, with germ tubes being 50 times more adherent than yeast cells. In addition, germinated yeasts were more susceptible to adherence inhibition by concanavalin A than non-germinated C. a/bicans [27]. Sobel eta/.…”
Section: Species and Strainsmentioning
confidence: 99%
“…Sandin et a/. [27] demonstrated that mannose-containing moieties on the surface of C. albicans and BEC could mediate adherence in vitro.…”
Section: Cell Surfacementioning
confidence: 99%
“…During the initial stages of infection the formation of hyphae may promote the adherence and penetration of host tissues. The induction of germ-tubes and hyphae has been shown to induce a 50-fold increase in binding to oral epithelial cells (Sandin et al, 1982). The promotion of apical expansion in germ-tube formation and the expression of cell surface antigens appears to be coordinately regulated (Chaturvedi et al, 1994) which may enable hyphae to attach firmly while penetration of host tissues is facilitated by the secretion of hydrolytic enzymes.…”
Section: Hyphal Transformationmentioning
confidence: 99%